Recovery from Long COVID: How College Students Thrive During Lockdown - Alisa Mar Cabacungan; Klent Rodni Mundog Delima; Jo Niza Boldero Mortiz; Loressa Joy De Claro Paguta; Ruel Billones (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
The Long COVID-19 Syndrome affected the lives of college students on lockdown for almost two years (2020-202), is the focus of this paper. Specifically, this study examined their stress, anxiety, depression levels, and psychosocial factors (socioeconomic status, adverse childhood experiences, and perceived social support) were related to these mental health issues. The impact of the Long COVID-19 on the students’ well- being and their coping mechanisms were explored. Using a cross- sectional survey research design, 600 students from different areas in Mindanao (southern islands of the Philippines) participated in this study. Results showed that the majority of the respondents reported no stress (78%), no anxiety (38%), and no depression (44.80%) during the lockdown. Moreover, a significant positive relationship appeared between adverse childhood experiences (ACEs) and levels of stress (p <0.001), anxiety (p <0.001), and depression (p <0.001). These findings suggest that adverse childhood experiences increase and the risk of other mental health issues increases. Results also suggest a significant negative relationship between perceived social support and levels of stress (p <0.05) and depression (p <0.05). The intersection of learning in higher education and mental health suggests the correlates of stress, ACE, and anxiety.